2003
DOI: 10.1038/sj.bjc.6600781
|View full text |Cite
|
Sign up to set email alerts
|

EORTC Early Clinical Studies Group early phase II trial of S-1 in patients with advanced or metastatic colorectal cancer

Abstract: Cancer of the colon and rectum is one of the most frequent malignancies both in the US and Europe. Standard palliative therapy is based on 5-fluorouracil/folinic acid combinations, with or without oxaliplatin or irinotecan, given intravenously. Oral medication has the advantage of greater patient convenience and acceptance and potential cost savings. S-1 is a new oral fluorinated pyrimidine derivative. In a nonrandomised phase II study, patients with advanced/metastatic colorectal cancer were treated with S-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 29 publications
(28 reference statements)
3
49
0
Order By: Relevance
“…S-1 was approved in Japan for AGC under an accelerated approval regulation system in 1999, and for head and neck cancer in 2001, and clinical trials against colorectal (Ohtsu et al, 2000), breast (Sano et al, 2000), and lung cancer (Kawahara et al, 2001) are now ongoing and high responses have been reported. The phase II studies of S-1 against gastric (Chollet et al, 2003) and colorectal cancer (den Brande et al, 2003) in Europe by EORTC-Early Clinical Study Group also revealed high efficacy. Therefore, S-1 can be anticipated to be one of the key drugs for AGC.…”
mentioning
confidence: 99%
“…S-1 was approved in Japan for AGC under an accelerated approval regulation system in 1999, and for head and neck cancer in 2001, and clinical trials against colorectal (Ohtsu et al, 2000), breast (Sano et al, 2000), and lung cancer (Kawahara et al, 2001) are now ongoing and high responses have been reported. The phase II studies of S-1 against gastric (Chollet et al, 2003) and colorectal cancer (den Brande et al, 2003) in Europe by EORTC-Early Clinical Study Group also revealed high efficacy. Therefore, S-1 can be anticipated to be one of the key drugs for AGC.…”
mentioning
confidence: 99%
“…Thus, the findings of the current study indicate that S-1 is a promising agent that has the potential to become a valuable oral treatment option, along with capecitabine and UFT ϩ LV, for patients with colorectal carcinoma. Clinical studies of S-1 in the treatment of metastatic colorectal and gastric malignancies 33,34 also suggest that S-1 possesses superior therapeutic activity compared with other regimens.…”
Section: Discussionmentioning
confidence: 99%
“…In phase II trials of S-1 as a single agent, response rates ranging from 19 to 39% were obtained in patients with advanced colorectal cancer [11][12][13]. These studies demonstrated that S-1 had a high response rate and good compliance in patients with advanced colorectal cancer treated on an outpatient basis.…”
mentioning
confidence: 82%